PENGGUNAAN JASA PERBANKAN SYARIAH SEBAGAI UPAYA MENINGKATKAN SHARIAH FINANCIAL INCLUSION (STUDI PADA MAHASISWA UNIVERSITAS MUHAMMADIYAH MAKASSAR): Studi Pada Mahasiswa Universitas Muhammadiyah Makassar - Wulandari Buamona; Muhammad Najib Kasim; Agusdiwana Suarni (LPPM Universitas Sains dan Teknologi Komputer, 2025)
This study aims to describe how the use of Islamic banking services contributes to enhancing shariah financial inclusion among students of Universitas Muhammadiyah Makassar. The research employed a qualitative descriptive approach involving eight student informants from various faculties selected through purposive sampling. Data were collected through in-depth interviews, non-participant observations, and documentation during May-July 2025. Data analysis followed the stages of reduction, presentation, and conclusion drawing in an interactive manner. The findings indicate that most students understand the basic principles of Islamic finance (prohibition of riba, profit-sharing, clarity of contracts, and transparency), although financial literacy is not evenly distributed. Experiences in using Islamic banking services were generally positive, with account opening procedures and contractual clarity being well appreciated.